Silicon nanowire networks for multi-stage thermoelectric modules. (15th May 2015) - Norris, Kate J.; Garrett, Matthew P.; Zhang, Junce; Coleman, Elane; Tompa, Gary S.; Kobayashi, Nobuhiko P.
Graphical abstract: Highlights: Fabricated flexible single, double, and quadruple stacked Si thermoelectric modules. Measured an enhanced power production of 27%, showing vertical stacking is scalable. Vertically scalable thermoelectric module design of semiconducting nanowires. Design can utilize either p or n-type semiconductors, both types are not required. Δ T increases with thickness therefore power/area can increase as modules are stacked. Abstract: We present the fabrication and characterization of single, double, and quadruple stacked flexible silicon nanowire network based thermoelectric modules. From double to quadruple stacked modules, power production increased 27%, demonstrating that stacking multiple nanowire thermoelectric devices in series is a scalable method to generate power by supplying larger temperature gradient. We present a vertically scalable multi-stage thermoelectric module design using semiconducting nanowires, eliminating the need for both n-type and p-type semiconductors for modules.